The Macrostructure of Al-40Sn Alloy and Its Tribological Properties under Dry Friction; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Rusin N. M. (2016, 2016)
Title screen